Ethnography and Values of Character Education at Kompas Academy (Combination of Pencak Sitembak) - Adnyana, Kadek Tri; Astra, I Ketut Budaya; Suwiwa, I Gede (Indonesian Values and Character Education Journal, 2022)
The problem of human character, especially the younger generation, in this case students has become the main concern of the Indonesian nation. It is not only related to the sad empirical condition of the current national character, but also to the condition of the values ​​of Pancasila, which should be the identity of the nation's character. The aims of this study to analyze the values of character education at the Kompas Pencak Silat Academy. This research uses qualitative approach. Sources of information in this study can be classified into 2 (two) types, namely primary data, namely a collection of information obtained directly from the research location through the first source (respondents or informants, through interviews) and secondary data, namely data used to support primary data. The stages of data analysis techniques in this study are data reduction, data display, and drawing conclusion. The results of the study show character values ​​in pencak silat by caring for the training ground first, making sure that the training area is clean of garbage or so on before and after training, tidying up the items that have been used to their original places. In its establishment, this College of Kompas experienced ups and downs in the 1990-2000s and this college still upholds character values.